Influence of Cu-doped TiO2 on its structural and photocatalytic properties - Teodoro, Vinícius; Longo, Elson; Zaghete, Maria Aparecida; Perazolli, Leinig Antonio (Eclética Química, 2022)
Due to the potential of heterogeneous photocatalysis for wastewater treatment, the researches concerning the improvement materials modifications for its photocatalytic activity have been widely increased. One of the most employed methods is the metal doping into semiconductors. Herewith, we demonstrated the influence of Cu doping into TiO2 in its photocatalytic properties. The powder samples with 0.0 to 0.7% mol were obtained by the Pechini method and characterized by XRD, micro-Raman spectroscopy, FE-SEM, and photoluminescence spectroscopy. The Cu insertion into TiO2 structure induced the stabilization of anatase phase, increasing its content in the samples in relation to the bare TiO2. The PL results indicated that a decrease in the PL emission intensity and a shift of the emission band to the blue region. The photocatalytic activity for rhodamine B degradation under UV light irradiation indicated that the Cu-doping into TiO2 led to an enhancement of the photocatalytic activity compared to the bare one.